2021
DOI: 10.5194/acp-2020-1227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurement report: An assessment of the impact of a nationwide lockdown on air pollution – a remote sensing perspective over India

Abstract: Abstract. The nationwide lockdown was imposed over India from 25th March to 31st May 2020 with varied relaxations from phase-I to phase-IV to contain the spread of COVID-19. Thus emissions from industrial and transport sectors were halted during lockdown (LD) which resulted in a significant reduction of anthropogenic pollutants. The first two lockdown phases were strictly followed (phase-I and phase-II) and hence are considered as total lockdown (TLD) in this study. Satellite-based tropospheric columnar nitrog… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The Aerosol Optical Depth (AOD) is a proxy of atmospheric pollution level, which measures how light is attenuated by suspended particles through the atmosphere. During the COVID-19 lockdowns, satellite-derived AOD data revealed that the aerosol levels reduced substantially by 40–60% across urban areas in south and southeast Asia ( Kanniah et al, 2020 ; Pathakoti et al, 2021 ; Ranjan et al, 2020 ). Recent works also revealed a large reduction in BC levels, as well as significant modulations in aerosol scattering and absorption properties enabling to modify the radiation budget and temperature at the surface and in the lower atmosphere ( Anil & Alagha, 2020 ; Kaskaoutis et al, 2021 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Aerosol Optical Depth (AOD) is a proxy of atmospheric pollution level, which measures how light is attenuated by suspended particles through the atmosphere. During the COVID-19 lockdowns, satellite-derived AOD data revealed that the aerosol levels reduced substantially by 40–60% across urban areas in south and southeast Asia ( Kanniah et al, 2020 ; Pathakoti et al, 2021 ; Ranjan et al, 2020 ). Recent works also revealed a large reduction in BC levels, as well as significant modulations in aerosol scattering and absorption properties enabling to modify the radiation budget and temperature at the surface and in the lower atmosphere ( Anil & Alagha, 2020 ; Kaskaoutis et al, 2021 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Satellite-based remote sensing provides extensive coverage and allows for the monitoring of air pollution on a global scale. It measures various parameters, including aerosol optical depth, tropospheric ozone, and nitrogen dioxide concentrations (Demetillo et al, 2020;Chudnovsky, 2021;Muthukumar et al, 2021;Pathakoti et al, 2021;Roy, 2021;Xiong et al, 2021;Ji et al, 2022;Scheibenreif et al, 2022;Zhu et al, 2022;Zhang et al, 2022;Abu El-Magd et al, 2023;Wang et al, 2023). Ground-based remote sensing techniques, such as lidar and sun photometry, provide detailed information about the vertical profiles of pollutants and can be used to validate satellite measurements.…”
Section: Analytical Techniques For Measuring Air Pollutionmentioning
confidence: 99%